Effect of spacing on the early performance of selected Bamboo species at a mid hill of Arunachal Pradesh - Singh, K.A.; Sarangi, S.K.; Shukla, R.B. (Indian Journal of Agroforestry, 2020)
Effects of three clump densities in square planting geometry i.e., 400 (5m x 5 m), 278 (6m x 6m) and 204 (7m x 7m) clumps/ha were studied on various yield attributing characteristics of 13 bamboo species viz. Bambusa arundinacea, B. balcooa, B. cacharensis, B. nutans, B. pallida, B. tulda, Cephalostachyum  pergracile, Dendrocalamus asper, D. giganteus, D. hamiltonii, D. hookerii, D. sahnii and D. sikkimensis during 2002-2006 in North Eastern Hill region of India. Considering the productivity of culms after five years of planting, 5m x 5 m spacing was found suitable for B. arundinacea, B. cacharensis, B. nutans and D. hamiltonii; 6m x 6m for D. giganteus, D. sahnii, D. sikkimensis; 7m x 7m for B. balcooa, B. pallida, B. tulda, D. asper, D. hookerii and C. pergracile. All the bamboo species showed significant variation in clump circumference due to interactions between planting density and bamboo species. B. cacharensis and, D. sahnii in general had maximum circumference of clump and also produced highest number of culms per clump. The culm diameter was not affected by different densities of planting.